Needs Analysis of Differentiation Learning Design with a Sustainability-Oriented TPACK Approach on Climate Concept Phase D Natural Science Material - Dewi, Ikasari; Roshayanti, Fenny; Rita Sulistya Dewi, Endah; Rita Sulistya Dewi, Endah (KnE Social Sciences, 2024)
Climate change is an increasingly real problem. One route that can be taken to overcome this problem is through education. Learning as the core of education needs to be designed in such a way that students receive sufficient provisions to be able to participate in overcoming climate change. This research aims to analyze the need for learning designs for climate change concepts. The method used in this research is a qualitative research method. The partcipants in this research were 30 science teachers in Pekalongan city. Data collection was carried out using interview techniques, documentation, and questionnaires. Data analysis techniques were done through data reduction, data presentation, and drawing conclusions. The data obtained shows that the depth of material in climate change learning is still lacking, learning is not yet differentiated, the use of information technology is still minimal, discussions are still focused on environmental aspects and have not been linked much to economic and environmental aspects. The findings in this research indicate the need for a climate change concept learning design with sufficient material scope and depth, accommodating the diversity of student characteristics, and introducing a sustainability perspective for sustainable development. Keywords: needs analysis, learning design, climate change, natural science, Phase D.